Effect of Dietary Incorporation of Hemp Seeds Alone or with Dried Fruit Pomace on Laying Hens’ Performance and on Lipid Composition and Oxidation Status of Egg Yolks - Daniel Mierlita; Alin Cristian Teușdea; Mădălina Matei; Constantin Pascal; Daniel Simeanu; Ioan Mircea Pop (Animals, 2024)
The present study was conducted to investigate the effects of introducing hemp seeds, as a source of PUFAs, into a standard diet with or without dried fruit pomace (dried blackcurrant (DB) or dried rosehip (DR)), as a source of natural antioxidants, on the laying performance of hens and the FA profile, cholesterol level, antioxidant content, and lipid oxidative status in the yolks of fresh eggs or eggs stored at 4 °C for 28 days. The experiment used 128 Tetra SL hens at 35 weeks of age, which were divided into four groups and randomly assigned to four dietary treatments: a standard corn–wheat–soybean meal diet (C), standard diet containing 8% ground hemp seed (H), hemp seed diet containing 3% dried blackcurrant pomace (HB), and hemp seed diet containing 3% dried rosehip pomace (HR). The laying rate, feed conversion ratio (FCR), egg weight, and yolk weight were improved by the use of hemp seeds. The yolks of the H, HB, and HR eggs had a lower cholesterol (p ˂ 0.01) and SFA content, while the concentration of total and individual PUFAs (n-6 and n-3 FAs) was significantly higher (p ˂ 0.01) compared to C. In addition, the introduction of hemp seeds into the diets alone or with dried fruit pomace (DB or DR) led to increased (p ˂ 0.001) content of α-linolenic acid (ALA, 18:3n-3), eicosapentaenoic acid (EPA, 20:5n-3), and docosahexaenoic acid (DHA, 22:6n-3) and hypo-/hypercholesterolemic FA ratio and decreased arachidonic acid (AA, 20:4n-6) content, n-6/n-3 ratio, and thrombogenicity index (TI) compared to the control eggs. The introduction of dried fruit pomace (DB or DR) into the diets had no effect on the laying performance of the hens or the cholesterol content and FA profile of the egg yolks, compared to the diet supplemented only with hemp seeds. The dried fruit pomace improved the color, accumulation of antioxidants, and oxidative stability of fats in the yolks of the fresh eggs and eggs stored at 4 °C for 28 days. The DR was found to have the most desirable effects, producing the most intense color of egg yolks, the highest content of natural antioxidants, and the best oxidative stability of yolk lipids.